2010
DOI: 10.1063/1.3465547
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen refinement during solid phase epitaxy of buried amorphous silicon layers

Abstract: The effect of hydrogen on the kinetics of solid phase epitaxy ͑SPE͒ have been studied in buried amorphous Si layers. The crystallization rate of the front amorphous/crystalline ͑a/c͒ interface is monitored with time resolved reflectivity. Secondary ion mass spectrometry ͑SIMS͒ is used to examine H implanted profiles at selected stages of the anneals. The H retardation of the SPE rate is determined up to a H concentration of 2.3ϫ 10 20 cm −3 where the SPE rate decreases by 80%. Numerical simulations are perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Several previous papers reported that carbon and hydrogen with percentage-order concentrations decrease the velocity of SPEG. [28][29][30][31][32] k B is the Boltzmann constant, and T is the absolute temperature in the subsequent thermal annealing treatment. The parameters used for MC ion implantation and KMC recrystallization simulation are summarized in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous papers reported that carbon and hydrogen with percentage-order concentrations decrease the velocity of SPEG. [28][29][30][31][32] k B is the Boltzmann constant, and T is the absolute temperature in the subsequent thermal annealing treatment. The parameters used for MC ion implantation and KMC recrystallization simulation are summarized in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…It is thus of technological importance that not only the H content is accurately determined in the material but also its depth distribution and kinetic properties be established. For low H concentrations, H diffusion is often determined by secondary ion mass spectroscopy [4]. In a-Si:H and a-Si 1-x C x :H, Fourier transform infrared spectroscopy is widely used to quantify and assign IR active vibrations bonds.…”
Section: Introductionmentioning
confidence: 99%